2016
DOI: 10.1242/bio.017517
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a cystine transporter downregulates expression of genes involved in sulfur regulation and cellular respiration

Abstract: Cystine and cysteine are important molecules for pathways such as redox signaling and regulation, and thus identifying cellular deficits upon deletion of the Saccharomyces cerevisiae cystine transporter Ers1p allows for a further understanding of cystine homeostasis. Previous complementation studies using the human ortholog suggest yeast Ers1p is a cystine transporter. Human CTNS encodes the protein Cystinosin, a cystine transporter that is embedded in the lysosomal membrane and facilitates the export of cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…We manually confirmed the synthetic genetic interaction of cfs1 Δ with ric1 Δ or rgp1 Δ. The ric1 Δ and rgp1 Δ mutants show temperature-sensitive growth (Mizuta et al 1997; Siniossoglou et al 2000) (Figure 8A). They grew as well as the wild-type strain at 30°, whereas the cfs1 Δ mutation caused severe growth defects in these mutants at this temperature (Figure 8A).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We manually confirmed the synthetic genetic interaction of cfs1 Δ with ric1 Δ or rgp1 Δ. The ric1 Δ and rgp1 Δ mutants show temperature-sensitive growth (Mizuta et al 1997; Siniossoglou et al 2000) (Figure 8A). They grew as well as the wild-type strain at 30°, whereas the cfs1 Δ mutation caused severe growth defects in these mutants at this temperature (Figure 8A).…”
Section: Resultsmentioning
confidence: 82%
“…Ypt6p, the yeast counterpart of mammalian Rab6 GTPase, functions in endosome-to-TGN and intra-Golgi retrograde transport (Luo and Gallwitz 2003), together with its guanine nucleotide exchange factor (GEF), the Ric1p/Rgp1p complex (Siniossoglou et al 2000). We manually confirmed the synthetic genetic interaction of cfs1 Δ with ric1 Δ or rgp1 Δ.…”
Section: Resultsmentioning
confidence: 99%
“…Ers1 localizes to the vacuole membrane and whereas Ers1-deficient yeast cells show sensitivity to the antibiotic hygromycin B, expression of human CTNS in these cells can complement the hygromycin B sensitivity and confer resistance [198]. Recently, it was demonstrated that Ers1 can transport cystine, although intracellular cystine does not increase in ers1Δ cells [199], possibly indicating the presence of redundant, as yet unidentified, cystine transporters. Additional PQ-loop family members Ypq1, Ypq2, and Rtc2 also localize to the vacuole membrane, and it is proposed that they export basic amino acids such as lysine, arginine, and/or histidine [200].…”
Section: Efflux Of Amino Acidsmentioning
confidence: 99%
“…A comparative transcriptomic analysis of ers1Δ strains implicated sulfur homeostasis as aberrant, which was consistent with the gene expression profile of cystinotic cells from cystinosis patients. Additionally, energy production, oxidative stress, calcium and potassium transport and stress response were also awry in this mutant model 85 . A high copy suppressor screen in yeast identified that MEH1 , a gene critical for the process of microautophagy and the function of amino acid permease Gap1p that mediates cysteine uptake, suppressed hygB sensitivity in the ers1Δ yeast model 84 86 .…”
Section: Budding Yeast As a Genetic Model Of Lsdsmentioning
confidence: 90%